Social movements against authoritarian subnational governments. The case of social protests against juarismo in Santiago del Estero, Argentina (2003 – 2004) - Carabajal, José Daniel (2020)
In the present work, the marches in justice claim for the “Double crime of La Dársena” and its possible incidence in the termination of the juarista regime in 2004 in the province of Santiago del Estero are analyzed. Said regime ended its mandate through the Federal Intervention decreed by the National Congress after the aforementioned crimes that exposed the irregularities and abuses of power of this government. On that occasion, from different sectors of society, protest marches were created in the demand for justice that concentrated the attention of the national media and the National Government itself on Santiago del Estero. For this article, no less than ten interviews were conducted with participants and organizers of these marches, to then perform a content analysis in matrices. Tarrow's perspective was adopted as the main theoretical line, and the main claims of the different political and social sectors that mobilized a part of civil society in the province were described. Likewise, they inquired about the possible incidence, and how they did it, of the marches at the end of the Juarismo. It should be noted that the nationalization of the protest and the presence of the national media made the opening of said regime possible, enabling the arrival of Federal Intervention to the province. This was possible thanks to a sum of factors that came together (political opportunity, lack of understanding between the national and subnational governments, violation of Human Rights, etc.) so that the national government could make the political decision to oust the Juarista regime from power.